The role of local authorities in community development and in the implementation of the reconstruction and development program (RDP) - Rosenberg, Shirene Amilia (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1995.